Groundwater Potential Zonation Through Integration of Remote Sensing, Geographic Information Systems and AHP Techniques in FCT Abuja - Farouq Ado Umar; Mallam Abu; Osagie Abel U. (Science & Technology Asia, 2026)
Groundwater is a vital freshwater resource supporting domestic, agricultural, and industrial demands, especially in semi-arid regions with limited surface water. This study maps groundwater potential zones in the Federal Capital Territory (FCT), Abuja, Nigeria, using an integrated approach combining Remote Sensing (RS), Geographic Information Systems (GIS), and the Analytical Hierarchy Process (AHP). These methods enable wide spatial coverage and objective analysis where conventional data are scarce. The study uses thematic datasets—slope, drainage density, lineament density, rainfall, topographic wetness index (TWI), land use/land cover (LULC), geology, and soil type—derived from satellite imagery, government sources, and field surveys (2015–2024). Parameters were weighted with AHP, processed in ArcGIS 10.7.1, and overlaid to produce a composite groundwater potential map. Results show steep slopes dominate over 80% of the area, limiting recharge, while only 2.29% favors infiltration. Moderate to low drainage density supports balanced recharge, while higher densities restrict it. Moderate lineament density aids recharge, though highdensity zones risk contamination. Most areas have low TWI, with small recharge hotspots. Vegetation dominates land cover, supporting infiltration, while urbanization hinders it. Overall, the model identifies high, moderate, and low potential zones, supporting sustainable groundwater management.